The Monocarboxylate Transporter SLC16A6 Regulates Adult Length in Zebrafish and Is Associated With Height in Humans - Karanth, Santhosh; Schlegel, Amnon (Frontiers in Physiology, 2019)
When fasted as larvae or fed ketogenic diets as adults, homozygous zebrafish slc16a6a mutants develop hepatic steatosis because their livers can not export the major ketone body β-hydroxybutyrate, diverting liver-trapped ketogenic carbon atoms to triacylglycerol. Here we find that are longer than their wild-type siblings. This effect is largely not sexually dimorphic and nor is it affected by both fat content on a pure genetic background; a mixed genetic background alters the proportionality of mass to length modestly. We also observe that non-coding variations in the 5’-untranslated region and first intron, and coding variations within the fifth exon of the orthologous human gene locus SLC16A6 are highly significantly associated with human height. Since both zebrafish and human orthologs of SLC16A6 are expressed in multiple locations, this gene likely regulates height through modulating transport of monocarboxylic acids in several tissues.